+0  
 
0
72
1
avatar

thank you!

 May 5, 2020
 #1
avatar+111430 
+1

x  = 3  - t    ⇒ t  = 3 - x

 

When t  = - 3

 

x = 6   and  y  = 4  =   (6, 4)  =  initial point

 

When t  =  1

 

x = 2   and  y  =  4  =    (2, 4)  = terminal point

 

So

 

y  = (t + 1)^2

 

y  = (3 - x + 1)^2

 

y = (4 - x)^2  =  (x - 4)^2   +  0

 

The  vertex is (4, 0)

 

The  motion  is  right to left       { (2,4)  is  to the left of (6,4)  }

 

See the graph here  : https://www.desmos.com/calculator/hxfat2kymd

 

 

cool cool cool

 May 5, 2020

20 Online Users

avatar
avatar
avatar
avatar